Profit Sharing Ratios in Mudaraba Contracts Revisited (International Journal of Banking and Finance, 2010)
This paper examines three interlinked issues: First, what is the current state of profit sharing in Islamic banking, that is, is the division of profit between the banks and the depositors satisfactory? Second, can the profit sharing in a two-tier mudaraba contract give the same rate of return to depositors as the bank receives from the investment of their deposits in business? Finally, can the central bank use in some ways the profit sharing ratio along with the rate of interest as an instrument for credit control in a dual banking system? The answer to the fi rst two questions is in the negative. To the third, a tentative response is yes. The paper also suggests a policy tool the central banks can presumably use for controlling credit, more so in view of the recurring financial crises like the one emanating from the US that the world is facing today. The tool may in addition help improve the link between the banks and depositors by adopting an iniquitous distribution of profits.